Delirium in Internal Medicine Departments in a Tertiary Hospital in Israel: Occurrence, Detection Rates, Risk Factors, and Outcomes - Efraim, Nirit Tzur; Zikrin, Evgeniya; Shacham, David; Katz, Dori; Makulin, Evgeni; Barski, Leonid; Zeller, Lior; Bartal, Carmi; Freud, Tamar; Lebedinski, Svetlana; Press, Yan (Frontiers in Medicine, 2020)
Background: The aim of the study was to assess the occurrence rate of delirium among elderly hospitalized patients in the medicine wards of a large tertiary hospital, to identify risk factors, and to evaluate the diagnostic rate for delirium among the medical teams. Methods: A 3-month prospective study of patients 65 years of age and above in three medicine wards: in two wards patients were examined by trained study team members using the Confusion Assessment Method (CAM), while the third was a control ward where CAM was not administered. The third ward served to control for the effect of the presence of investigators in the other wards as a potential confounding factor. Based on the results of this assessment patients were defined as suffering from subsyndromal delirium, full delirium (these two groups were later combined into an “any symptoms of delirium” group), and no delirium. The rate of diagnosis by the medical team was obtained from the electronic medical records. Results: The full delirium rate was 5.1%, the rate of subsyndromal delirium was 14.6%, and the rate of any symptoms of delirium was 19.6%. Absence of a partner, pain, anemia, hyponatremia, hypocalcemia and the use of drugs with an anticholinergic burden were factors for any symptoms of delirium as well as for subsyndromal delirium. Subsyndromal delirium and any symptoms of delirium were associated with a reduced chance of being discharged to home and a higher three-month mortality rate. A diagnosis of delirium was found in only 19.4% of the patients with any symptoms of delirium in the medical records. Conclusions: Delirium is a common problem among elderly hospitalized patients, but it is diagnosed sub-optimally by the medical team. There is a need for further training of the medical teams and implementation of delirium assessment as part of the ward’s routine.